Core outcomes for adult burn survivors: A clinical overview - Falder, S.; Browne, Allyson; Edgar, D.; Staples, E.; Fong, J.; Rea, S.; Wood, F. (Pergamon Press, 2009)
Burn trauma ranges from the minor burn to the devastating injury, which can impact on all aspects of a person's life including aesthetic appearance, relationships with others and psychological, social and physical functioning. Measurement of outcome in burns patients is therefore complex and multi-faceted. The increasing numbers of major burn survivors implies that understanding health outcomes in these patients has assumed high priority. This paper sets out a conceptual framework for unifying outcome measurement, which may be useful to all members of the multidisciplinary team who are contemplating outcome assessment in their burn patients. It outlines seven core domains of assessment which are (i) skin; (ii) neuromuscular function; (iii) sensory and pain; (iv) psychological function; (v) physical role function; (vi) community participation; and (vii) perceived quality of life. Within each domain, we present a brief clinical review of the most commonly administered measurement tools that have been, or potentially could be, used to assess aspects of these core domains. Where possible, the psychometric properties and clinical utility of these tools are presented. A concise discussion of key methodological issues which should be addressed in this assessment process is then provided, together with suggestions for future research. © 2008 Elsevier Ltd and ISBI.